AMBIVALENCE IN JHUMPA LAHIRI’S THE LOWLAND: IRRESOLUTION OF IDENTITY (Universitas Pamulang, 2017)
Abstract This study is aimed to uncover ambivalence in Jhumpa Lahiri’s novel, entitled The Lowland. In this study, Lahiri portrays how ambivalence occurs to Indian immigrants. These Indian immigrants are described as individuals who have spent many years in America. They come to America to continue their study. It implies that they are educated people. However, they are not able to adapt American culture well. At the same time, they also dismiss some of their origin culture. As a result, Lahiri argues that these Indian immigrants face irresolution of identity. In addition, a concept of post-colonialism by Homi K. Bhabha is applied in this study. One of Bhabha’s ideas in his post-colonialism is called ambivalence. The result of this study discloses that there is a high possibility for immigrants to suffer for irresolution of identity as the effect of different and conflicting cultures they have to face. Keywords: ambivalence, irresolution of identity, immigrants, post-colonialism